Determination & comparison of maxillary first premolar pulp chamber landmarks using intraoral periapical radiograph and cone-beam computed tomography - Joshi Amatya, Neera; Prajapati, Kranti; Shrestha, Suraj; Wagle, Sharada (Journal of Chitwan Medical College, 2019)
Background: Dimension and location of pulp chamber are important during access cavity preparation. It allows clinician in instruments selection, orientation and depth of cutting during the process. Analysis of these has been done in preoperative intraoral periapical radiograph that gives two-dimensional image. The radiograph has been blamed now and then for the inaccurate results and iatrogenic damage occurred due to the inaccurate results. Cone-Beam Computed Tomography (CBCT) provides three-dimensional images and is taken as standard. Hence the aim of the study is to compare intra-oral periapical (IOPA) radiograph and CBCT to determine the landmarks for accurate results Methods: 50 intact two-rooted maxillary first premolars were collected and numbered. Periapical radiograph Images and CBCT images of these 50 teeth were taken and divided as; Group I: 50 IOPAR and Group II: 50 CBCT images. Landmarks marking and measurement was done using tracing paper and x-ray viewer for IOPA images and Planmeca Romexis software for CBCT images. Data were collected and analysed with descriptive and inferential statistics by using Statistical Package of Social Science (SPSS) software version 16. Results: The averages of group I are 7.44, 10.23mm 14.33mm, 4.1mm, 6.89mm and 2.79mm respectively. The averages of in group II are 6.95mm, 9.58mm, 14.03mm, 4.45mm, 7.07mm and 2.63mm respectively. There is statistically significant difference in measurement A and measurement B between group I and group II. Conclusions: This indicates that there are chances of overestimation of measurement A and B with IOPAR.